Business Communications Management on the Internet – Global Practices and Their Dimensions in Bulgaria - Mironova, Nadya; Harizanova, Elena (Research Papers, 2019)
Business communications management is challenged by the dynamic development of technologies and the Internet. Social networks, the Semantic Web 3.0, their impact on psycho-social processes, the formation of opinion, decision making and response, all those raise the question of how adequate the changes in business communications are. The purpose of this study is to analyse the interaction between organizations and digital reality on the world and European markets and to compare it with the Bulgarian practice through a comparative analysis of several influential international studies. The results reveal opportunities for increasing the efficiency of the communications of Bulgarian organizations in the digital environment. A model of innovations that support business communications in increasing their efficiency is proposed.